Nilai-Nilai dan Praktik Bisnis Etnis Tionghoa di Indonesia: Studi Literatur berdasarkan Teori Schwartz - Wijaya, Bagus Adinata Atmaja Sateng (Universitas Negeri Malang, 2025)
The Chinese ethnic group is one of the immigrant ethnic groups that has mostly carried out trading activities since the 18th century in Indonesia, so they have a good economic situation and have quite a large influence on the country's economy. However, the economic gap between the Chinese ethnic group and the natives has caused some prejudice. This study aims to understand the values and cultural practices of the Chinese ethnic group in the context of business in Indonesia, so that it can reduce prejudice and promote better collaboration with the Chinese ethnic group. This study was conducted using a literature study method using Google Scholar as a database with the keywords